2020
DOI: 10.1530/eje-19-0587
|View full text |Cite
|
Sign up to set email alerts
|

Impact of total thyroidectomy on quality of life at 6 months: the prospective ThyrQoL multicentre trial

Abstract: Objective This study is to determine the impact of complications after total thyroidectomy on health-related quality of life (HR-QoL) and to identify significant predictive factors of HR-QoL changes. HR-QoL is usually impaired in patients with thyroid diseases compared to the general population. Thyroidectomy is largely performed in the case of benign thyroid benign and can be associated with long-term complications (vocal cord palsy, hypoparathyroidism). Design The prospective ThyrQoL multicenter trial (NCT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 52 publications
3
16
0
5
Order By: Relevance
“…As presented in Table 1 , diagnostic surgery was performed after a median of 1.8 months in patients with benign histopathology and 1.9 months in patients with malignancy. Our findings are in line with previous studies that demonstrated a temporary decrease in HRQoL following thyroid surgery and subsequent improvement up to 12 months postoperatively, including an improvement in goitre symptoms and anxiety ( 10 , 13 , 14 , 15 , 16 , 17 , 23 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…As presented in Table 1 , diagnostic surgery was performed after a median of 1.8 months in patients with benign histopathology and 1.9 months in patients with malignancy. Our findings are in line with previous studies that demonstrated a temporary decrease in HRQoL following thyroid surgery and subsequent improvement up to 12 months postoperatively, including an improvement in goitre symptoms and anxiety ( 10 , 13 , 14 , 15 , 16 , 17 , 23 ).…”
Section: Discussionsupporting
confidence: 93%
“…HRQoL has been studied extensively in both benign and malignant thyroid diseases and is often impaired as compared to the general population ( 10 , 11 , 12 ). Thyroid surgery negatively affects short-term HRQoL, recovering as the time since surgery passes ( 10 , 13 , 14 , 15 , 16 , 17 ). The consequences of surgery, including long-term postoperative thyroid hormone substitution therapy, potential voice changes, scar cosmesis, and surgical complications such as permanent hypoparathyroidism and vocal cord paralysis, also impair HRQoL ( 10 , 18 , 19 , 20 , 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…Quality of life is the perception of individuals in the context of cultures and value systems in which they live and the state of quality of life is associated with their goals, expectations, standards, and concerns 24 . HRQoL is a multidimensional concept that includes physiological functions, psychological functions, role activities, social adaptability and overall feelings about health 25 . The SF-36 is a universal scale with eight domains for life quality assessment used in tumor patients and the control population.…”
Section: Discussionmentioning
confidence: 99%
“…They found only half of the patients who started ATD for initial treatment would avoid definitive treatment and only 40% would not need thyroid medication to achieve a euthyroid state. Moreover, studies focusing on QoL have all reported improved QoL following surgery 36–38 . Scerrino et al 36 compared the QoL results of 57 patients undergoing surgery for GD to a control group of patients using ATD.…”
Section: Referral For Surgery In the Treatment Of Gdmentioning
confidence: 99%
“…Moreover, studies focusing on QoL have all reported improved QoL following surgery. [36][37][38] Scerrino et al 36 compared the QoL results of 57 patients undergoing surgery for GD to a control group of patients using ATD. Patients following surgery demonstrated significant improvement in all fields assessed in the questionnaire.…”
Section: Referral For Surgery In the Treatment Of Gdmentioning
confidence: 99%